Bioequivalence Study of Two Capsule Formulations Containing Diacerein 50 mg in Healthy Human Subjects - Chakrabarty, Uday S; Mandal, Uttam; Bhaumik, Uttam; Chatterjee, Bappaditya; Ghosh, Animesh; Bose, Anirban; Pal, Tapan K (Arzneimittelforschung, 2008)
This study presents the results of a two-way, two-period, two-treatment crossover investigation in 12 healthy Indian male subjects to assess the bioequivalence of two oral formulations containing 50 mg of diacerein (CAS 13739-02-1). Both formulations were administered orally as a single dose separated by a one-week washout period. The content of diacerein in plasma was determined by a validated HPLC method with UV detection. The formulations were compared using the parameters area under the plasma concentration-time curve (AUC0–t), area under the plasma concentration-time curve from zero to infinity (AUC0–∞), peak plasma concentration (Cmax), and time to reach peak plasma concentration (tmax). The results of this study indicated that there were no statistically significant differences between the logarithmically transformed AUC0–∞ and Cmax values of the two preparations. The 90% confidence interval for the ratio of the logarithmically transformed AUC0–t, AUC0–∞ and Cmax were within the bioequivalence limit of 0.8–1.25 and the relative bioavailability of the test formulation was 96.63% of that of the reference formulation. Thus, these findings clearly indicate that the two formulations are bioequivalent in terms of rate and extent of drug absorption.
Keywords: Antiarthritics; CAS 13739-02-1; Diacerein, bioequivalence, pharmacokinetics